2002
DOI: 10.1063/1.1515770
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of dominant propagation of the ion-acoustic slow mode in a negative ion plasma and its application

Abstract: Different characteristics of ion acoustic waves were experimentally observed in two types of Xe+–F− double plasmas at different electron temperatures. For the lower electron temperature (around 0.15 eV), the slow mode, which had been considered not to dominate the wave propagation, was found to be dominant rather than the fast mode, which was observed to be dominant for the higher electron temperature (around 1.5 eV). According to the previous numerical investigation [Phys. Plasmas 8, 4275 (2001)], the new wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(67 citation statements)
references
References 22 publications
0
57
0
Order By: Relevance
“…The selected parameters values are inspired by the recorded recent experimental data of multicomponent plasma experiments [21][22][23][24]28], though we focus on the case of heavier negative ion magnetized multicomponent plasma Ar + -SF Figure 1 shows the oblique collision of two nonlinear IASWs which results as rarefaction of negative ion number density. It is shown that when two IASWs obliquely collide, a new nonlinear wave is formed during their collision (i.e., blue region) which moves ahead of the colliding IASWs; both its amplitude and width are larger than those of colliding IASWs, as depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected parameters values are inspired by the recorded recent experimental data of multicomponent plasma experiments [21][22][23][24]28], though we focus on the case of heavier negative ion magnetized multicomponent plasma Ar + -SF Figure 1 shows the oblique collision of two nonlinear IASWs which results as rarefaction of negative ion number density. It is shown that when two IASWs obliquely collide, a new nonlinear wave is formed during their collision (i.e., blue region) which moves ahead of the colliding IASWs; both its amplitude and width are larger than those of colliding IASWs, as depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Negative ions have been detected in the Earth's ionosphere [18], cometary comae [19], and the upper regions of Titan [20]. Moreover, multicomponent plasmas, such as Ar/SF 6 and K/SF 6 plasmas, are generally used to perform basic research on IASWs in dc discharge devices and Q-machines [21][22][23][24][25][26][27][28]. Since the early space observations [29], it has been admitted that the Maxwellian distribution is not always a realistic distribution [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…[15]. Similarly positrons can be generated in modern laser plasma experiments when ultra-intense laser pulse interacts with matter [16,17].…”
Section: Introductionmentioning
confidence: 98%
“…Plasmas containing a fraction of negative ions possess characteristic dynamical properties that may differ substantially from those of "traditional" (textbook) electronion plasmas. Such plasmas have been generated in the laboratory by using a Q-machine [7,8], a double plasma device [9][10][11], electron cyclotron resonance (ECR) based plasma devices [12,13] and specially designed discharge chambers [14]. Negative ion plasmas (NIP) have also been observed in Space environments, e.g.…”
Section: Introductionmentioning
confidence: 99%